Diseño y construcción de un banco de refrigeración para el AEIRNNR. - Eras Pasiche, Santos (2007)
The present work is titled: "Design and Construction of a Bank of Refrigeration for the AEIRNNR". The object of this work is to provide to the student of a didactic bank that reinforces the knowledge imparted in the classroom it has more than enough Refrigeration and its application in domestic, commercial and industrial systems, explaining and illustrating the most modern methods in installation, maintenance, I diagnose and repair. One of the most important characteristics in our work is to make stress in the concepts, theories and technical that are required for the knowledge of most of the manufactured team and used in the industries. The present investigation work contains practical of very interesting laboratory, some of which are: operation of a system of loaded capillary tube usually, operation of a system of expansion valve, errors of the coolant system taken place externally, etc. For that exposed, this work is an excellent laboratory manual for the courses that are imparted on the matter in the AEIRNNR. Also, it is one it magnifies consultation work for the specialist professionals in this area.